Aspectos da biologia e do controle químico de Spermacoce verticillata L. - Fadin, Dauri Aparecido (Universidade Federal de São Carlos, 2017)
Weed control is an essential practice in cropmanagement. However, the use of herbicides may not be effective in some situations, ranging from problems in application technology to the selection of tolerant individuals and resistant biotypes. In the State of Bahia, Brazil, in cotton producing areas, Spermacoce verticillata (buttonweed) is not being controlled during burndownapplications. The objective of this project was to determine herbicide control options at different stages of development of plants, to verify the morphological aspects of the leaf surface of this weed and to observe the absorption and translocation of glyphosate by the plant. In a first experiment, the control of the plants with different herbicides was tested in the phenological stages of 2-4 true leaves, 4-6 true leaves and in the emission of floral buds, characterizing the application in post-initial, post-normal and post respectively. The experiment consisted of 19 treatments arranged in a completely randomized design, where the visual control of plants (%) was evaluated at 7, 14, 21, 28, 35 and 42 days. At 42 days, the remaining plants were dried and dry weight was recorded. These data were analyzed by the F test, which when significant, had their means compared by the Tukey test at 5% significance. In a second experiment, the foliar absorption and glyphosate translocation were analyzed by the use of the C14 technique in different phenological stages of plant development. This evaluation was performed for different periods after application (4, 6, 8, 12 and 48 hours) in the different parts of the plant (leaves above and below the application, stems and roots). In these same periods, the plants were radiographed. In a third experiment, the anatomy and leaf morphology of the species were analyzed through optical and scanning electron microscopy analyzes at the different stages of development of the species. The following characteristics were evaluated: total leaf blade thickness, chlorenchyma thickness, parenchyma thickness, cuticle and epidermal thickness on abaxial and adaxial surfaces, central rib height and width. Several chemical control options for S. verticillatta have been found, ranging from contact herbicides such as paraquat to systemic, as 2,4-D and glyphosate and several product mixtures with glyphosate. The sensitivity of the plant was altered according to the stage of development and the herbicide applied. Plants with more advanced stages of development (flowering) showed slower absorption of glyphosate herbicide and intermediate plants absorbed smaller total amounts of the herbicide (4-6 leaves). Translocation was also facilitated in new or old plants, mainly influenced by translocation above the point of application. The translocation to the roots was larger and faster for plants in a lower vegetative stage of development. With the evolution of the stages of development of S. verticillata the plants began to show reductions of their leaf thickness due to reductions of the abaxial epidermis, the measurements of the conducting vessels and their parenchyma. In more advanced stages (from 6 leaves) of development the leaves presented in their adaxial surface a smaller quantity of stomata and a greater quantity of trichomes. No links were found between these characteristics and the species differential susceptibility to glyphosate applications. However, plants of S. verticillata presented several morphoanatomical changes that can alter the absorption and translocation of herbicides in the different phenological stages.
Aspects of biology and chemical control of Spermacoce verticillata L.
Keywords: Anatomia vegetal; Carbono marcado; Controle químico; Vassourinha-de-botão; Vegetal anatomy; Carbon-14; Chemical control; Buttonweed; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA::MATOLOGIA